2002
DOI: 10.1080/10803548.2002.11076527
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the NIOSH Lifting Equation: A Psychophysical and Biomechanical Investigation

Abstract: Using the results of psychophysical and biomechanical experiments, NIOSH (National Institute for Occupational Safety and Health) Recommended Weight Limit (RWL), the Lifting Index (LI), the form of the asymmetry multiplier, and the criterion for compression force were investigated. Analysis of the results indicated a significant difference between the NIOSH RWL and the reported Maximum Acceptable Weight of Lift (MAWL). Contrary to the NIOSH lifting equation, the form of the asymmetry multiplier was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 2 publications
0
16
0
1
Order By: Relevance
“…Unfortunately, approximately 35% of lifting tasks and 63% of workers cannot be assessed by means of the RNLE owing to its strict parameters and equation restrictions22, 27, 28, 29, 30, 31, 32, 33 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, approximately 35% of lifting tasks and 63% of workers cannot be assessed by means of the RNLE owing to its strict parameters and equation restrictions22, 27, 28, 29, 30, 31, 32, 33 ) .…”
Section: Introductionmentioning
confidence: 99%
“…These effects are primarily based on psychophysical evaluation of the influence of lifting on self-perceived work load or fatigue within a few hours. Therefore, the ability of these directives to protect against LBP risks has been questioned 34 35. Besides, current directives do not assess long-term consequences, which has hampered the development of threshold limit values distinguishing between healthy and unhealthy lifting exposure at work 36.…”
Section: Introductionmentioning
confidence: 99%
“…The RNLE was compared with dynamic biomechanical models in several studies (Elfeituri & Taboun, 2002; Kee & Chung, 1996; Lavender, Andersson, Schipplein, & Fuentes, 2003). It was observed that for low-level lifting the RNLE under-represents increased peak-sagittal moment, which was estimated using a linked segment-dynamic biomechanical model (Lavender et al, 2003).…”
Section: Resultsmentioning
confidence: 99%